Determination of the Inhibition and Recovery of the Plasma, Cerebral Cortex and Hippocampus Acetylcholinesterase Activity in Male Paraoxon-Treated Rats - M Mohammadi, (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Organophosphorus (OP) compounds are highly toxic and are widely used as an insecticide in agriculture and domestic consumptions. Acetylcholinesterase (AChE) inhibition is the primary mechanism of acute in vivo toxicity of organophosphorus compounds. In the present study we evaluated inhibition and recovery of the plasma, cerebral cortex and hippocampus AChE activity and their correlations following systemic administration of three doses of paraoxon in three different time points in rat. METHODS: Eighty four male Wistar rats (200-270 g) were used in this study and divided into groups of seven. Animals were given a single intraperitoneal injection of corn oil (vehicle group) or one of the doses of paraoxon (0.1, 0.3, or 0.7 mg/kg) and AChE activity in the plasma, cerebral cortex, and hippocampus was measured at 30 min, 4 h, and 18 h after exposure using the modified method of Ellman.FINDINGS: Plasma and brain AChE activity was inhibited in a dose dependent manner by paraoxon. After 18 h, plasma AChE activity was recovered 32, and 42 percent (p<0.001) in animals exposed to 0.3, and 0.7 mg/kg paraoxon, respectively. 18 h after 0.7 mg/kg paraoxon, AChE activity was significantly recovered (p<0.001) in both brain areas (about 20%). Plasma AChE activity correlated significantly with both cerebral cortex and hippocampus AChE activity in rats treated with paraoxon (0.3 and 0.7 mg/kg).CONCLUSION: In both brain areas, paraoxon (only 0.7 mg/kg) inhibited AChE activity to induce seizure activity after 30 min. Inhibition of the plasma AChE activity can use as a marker of exposure only in severe toxicities with OP compounds.